PENGGUNAAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR DAN KEAKTIFAN SISWA - Rina Astuti; Nailina Najuba (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
The problem faced is that the learning outcomes and student activity in class VII MTs N 5 Boyolali are still low. This research aims to find out that the use of the Contextual Teaching and Learning (CTL) learning model can improve learning outcomes and student activity in learning. This type of research is descriptive qualitative which provides an overview of the application of the CTL learning model to improve learning outcomes and student activity. The design of this research is pre-experimental with a one group pretest-posttest design. The population and sampling were class VII students at MTs N 5 Boyolali, totaling 33 students. The method for collecting data on student learning outcomes is in the form of test sheets and questionnaires for student activity. The data analysis technique uses the N-gain score test to calculate the comparison of pretest and posttest scores. The research results show that the use of the CTL model is 61.38% effective in improving student learning outcomes. Apart from that, there was an increase in student activity by 84.4% of students actively participating in learning activities. It was concluded that the use of the CTL learning model can improve learning outcomes and student activity in learning